Cognitive behavioral therapy to reduce persistent postsurgical pain following internal fixation of extremity fractures (COPE): Rationale for a randomized controlled trial. Issue 2 (15th July 2019) - Nowakowski, Matilda E.; McCabe, Randi E.; Busse, Jason W.
ABSTRACT: Background : Approximately half of all patients who undergo surgical repair of extremity fractures report persistent postsurgical pain (PPSP) at 1-year post-surgery. Psychological factors such as anxiety, depression, catastrophization, poor coping, high somatic complaints, and pessimism about recovery are risk factors for the development of PPSP. It is possible that interventions such as cognitive behavior therapy (CBT) that target psychological factors may reduce the incidence of PPSP in this population. Aims : The current report reviews the role of psychological factors in the development of PPSP and discusses the rationale and protocol development for a multi-site randomized-controlled trial investigating the effectiveness of CBT in reducing PPSP in patients with surgically treated extremity fractures.